การวิเคราะห์ต้นทุนและผลตอบแทนจากการลงทุนปลูกมะพร้าวน้ำหอม ของเกษตรกรในพื้นที่อำเภอบ้านแพ้ว จังหวัดสมุทรสาคร - เปอร์เขียว ศศิธร; สุทธิเกียรติ สุนา; สถิตชัยทรัพย์ เสมอขวัญ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study investigated the financial dimensions of aromatic coconut cultivation in Ban Phaeo District, Samut Sakhon Province, Thailand, with three objectives: (1) to analyze production costs, (2) to evaluate financial returns, and (3) to assess investment feasibility. Primary data were collected through semi-structured interviews with 50 farmers, selected via purposive sampling with a minimum of one year of cultivation experience. Data were analyzed using descriptive statistics and cash flow analysis, based on a 20-year plantation lifespan and an 8 percent annual discount rate, in accordance with Boardman et al. (2018). Three principal findings emerged. First, the average total production cost was 21,850 baht per rai per year, comprising raw material costs of 9,420 baht (43.1 percent), labor costs of 8,750 baht (40.0 percent), and manufacturing overhead of 3,680 baht (16.9 percent), with direct material and labor costs representing 83.1 percent of total expenditure. Second, the average yield was 5,200 coconuts per rai per year at 11.20 baht per unit, generating gross revenue of 58,240 baht and net income of 36,390 baht per rai per year. Third, all financial indicators confirmed investment viability: NPV of 184,500 baht per rai, IRR of 18.6 percent exceeding the 8 percent discount rate, B/C Ratio of 1.84, and a payback period of 5.2 years. These results confirm that aromatic coconut cultivation in the study area is financially viable and capable of yielding sustainable long-term returns. However, price volatility and rising input costs remain significant risk factors requiring systematic management. The findings provide empirical evidence to support production planning, investment decision-making, and agricultural policy formulation at the local level.